Mode of miniaturisation influences body shape evolution in New World anchovies (Engraulidae). Issue 1 (2nd December 2019) - Bloom, Devin D.; Kolmann, Matthew; Foster, Kimberly; Watrous, Helen
Abstract: We explored the macroevolutionary dynamics of miniaturisation in New World anchovies by integrating a time‐calibrated phylogeny, geometric morphometrics and phylogenetic comparative methods. We found that the paedomorphic species Amazonsprattus scintilla occupies a novel region of shape space, while the dwarf species Anchoviella manamensis has an overall shape consistent with other anchovies. We found that miniaturisation did not increase overall clade disparity in size or shape beyond the expectations of Brownian motion, nor were there differences in rates of size or shape evolution among clades. Overall, our study shows that while the mode of miniaturisation influences shape evolution, the phenotypic novelty produced by the evolution of miniaturisation did not seem to alter macroevolutionary dynamics.